Qualitative research in applied situations: Strategies to ensure rigor and validity - N Nakkeeran; Sanjay P Zodpey (Wolters Kluwer Medknow Publications, 2012)
Traditionally, qualitative studies are founded on interpretative and constructive epistemology. The process of data collection in these studies is longer and intensive. This helps to build a strong rapport with the community, hence enabling to capture the field as naturally as possible. These characteristics provide an ample scope to take care of quality and validity of data. However, in applied situations, data collection is often a truncated activity. This robs away a number of taken-for-granted strengths of traditional qualitative research methods: No time is spent on rapport building; holism is left behind, instead we engage in selection; we focus narrowly on specific phenomenon of concern, divorced from its context; analysis does not evolve out of an iterative process. In this paper, we aim to discuss some of the issues related to rigor and quality of such studies and strategies available to address them.